PSXIII-13 Artificial insemination by estrus detection or by fixed-time in superovulated beef cows. (7th December 2018) - Forrest, D; Calloway, J; Riley, D; Steinhauser, C; Posey, D; Looney, C
Abstract: An analysis was conducted comparing embryo production following AI by estrus detection (ED) or fixed-time (FT) in superovulated beef cows. Overall, 1002 embryo collections from 407 donors from 2012–2016 were analyzed. Cows were assigned to one of four breed types (BT): American, Continental, English or Asian. Cows were stimulated by an Eazi-Breed ™ CIDR®, (1.38 g P4, Zoetis. Parsippany, NJ) with injection (i.m.) of P4 (25 mg) and E2-17β (2.5 mg, Medshop, Longview, TX) on Day 0. On day 4, FSH (Follitropin V ®, Vetoquinol, Brisbane, Australia or Pluset ®, MOFA, Verona, WI) was injected (i.m.) AM and PM for 3.5 d at decreasing doses (128–332 mg). On day 6, an injection (i.m.) of PGF2α (30 mg) or its analogue (375 mcg) was given AM and PM. On day 7 AM, CIDR was removed. Collections < January 20, 2015 were assigned to ED with a HeatWatch™ transmitter attached at CIDR removal. At onset of estrus, injection (i.m., 100 mcg) of GnRH (Cystorelin ®, Merial, Duluth, GA) was followed by AI 12 and 24 hr later with 3–4 units of frozen-thawed semen. All other collections were assigned to FT. GnRH (i.m., 100 mcg) was injrcted 24 hr after CIDR removal with AI 12 and 24 hr after GnRH. Effects of treatment, breed type and season on embryo response were analyzed by chi-square. FT donors had a greater proportion (P<0.01) of viable embryos and a lower proportion of degenerate embryos. The proportion that failed to stimulate differed among BT but not by season. Proportions of viable embryos, degenerate embryos and unfertilized ova were affected (P<0.01) by BT and season. We conclude AI of supersiimulated cows using FT is superior to ED, and embryo quality is influenced by BT and season.